2022
DOI: 10.3389/fimmu.2022.871564
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Implications of Angiogenesis and m6A Modification on Immunosuppression and Therapeutic Sensitivity in Low-Grade Glioma by Network Computational Analysis of Subtypes and Signatures

Abstract: Angiogenesis is a complex process in the immunosuppressed low-grade gliomas (LGG) microenvironment and is regulated by multiple factors. N6-methyladenosine (m6A), modified by the m6A modification regulators (“writers” “readers” and “erasers”), can drive LGG formation. In the hypoxic environment of intracranial tumor immune microenvironment (TIME), m6A modifications in glioma stem cells are predominantly distributed around neovascularization and synergize with complex perivascular pathological ecology to mediat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 105 publications
0
4
0
Order By: Relevance
“…An increasing number of studies have focused on the role of RNA m 6 A methylation in the development of various neurological diseases, such as Parkinson’s disease [ 23 ], Alzheimer’s disease [ 24 , 25 ], multiple sclerosis [ 26 ], tumours [ 27 , 28 , 29 ], epilepsy [ 30 ], and neuropsychiatric disorders [ 31 ]. However, to date, there is limited research focusing on the role of RNA m 6 A methylation in TBI and BGA.…”
Section: Discussionmentioning
confidence: 99%
“…An increasing number of studies have focused on the role of RNA m 6 A methylation in the development of various neurological diseases, such as Parkinson’s disease [ 23 ], Alzheimer’s disease [ 24 , 25 ], multiple sclerosis [ 26 ], tumours [ 27 , 28 , 29 ], epilepsy [ 30 ], and neuropsychiatric disorders [ 31 ]. However, to date, there is limited research focusing on the role of RNA m 6 A methylation in TBI and BGA.…”
Section: Discussionmentioning
confidence: 99%
“…This dynamic and reversible epigenetic modification affects the fate of RNA molecules and further regulates mammalian cell differentiation, immunity, and apoptosis. Studies have shown that the imbalance of m6A is involved in the development of gliomas [ 7 , 19 , 20 ]. M6A can regulate cell self-renewal, differentiation, invasion, and apoptosis by regulating gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, m6A modification in LGG is significantly associated with angiogenesis. Each of the 17 m6A regulators and 36 ARGs exhibited a significant self-positive correlation [ 20 ], and the researcher found that three m6a-lncRNAs, including ELOA-AS1, HOXB-AS1, and FLG-AS1, were closely related to the prognosis of LGG patients. Cancer cells can resist anoikis in several ways, such as by secreting growth factors, activating pro-survival signaling pathways, and altering integrin expression patterns [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the abnormal expression of m 6 A-related proteins may lead to the development of various neurological diseases, such as PD [ 145 , 146 , 147 ], AD [ 148 , 149 , 150 , 151 , 152 ], MS [ 153 ], tumours [ 154 , 155 , 156 ], epilepsy [ 157 ], and neuropsychiatric disorders [ 158 ]. TBI, as one of the major diseases of CNS, often causes memory problems in humans [ 159 ].…”
Section: M 6 a Rna Modification And Bgamentioning
confidence: 99%